2022
DOI: 10.1038/s41419-022-05093-0
|View full text |Cite
|
Sign up to set email alerts
|

RGS6 suppresses TGF-β-induced epithelial–mesenchymal transition in non-small cell lung cancers via a novel mechanism dependent on its interaction with SMAD4

Abstract: Regulator of G-protein signaling 6 (RGS6) is a newly discovered tumor suppressor that has been shown to be protective in development of various cancers such as breast cancer and bladder cancer. But the mechanisms underlying these tumor-suppressing functions of RGS6 are not fully understood. Here, we discover a novel function of RGS6 in suppressing TGF-β-induced epithelial–mesenchymal transition (EMT) of non-small cell lung cancer (NSCLC) cells and in vivo NSCLC metastasis. Using both bioinformatics and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ). Another tumor suppressor, regulator of G protein signaling 6 ( RGS6 ), is upregulated in the liver of NAFLD patients, forms a complex with ATM in the liver, promotes ATM phosphorylation, and drives hepatic steatosis ( 44 , 45 ). A study confirmed that hepatic RGS6 increases oxidative stress and inflammation, which drive lipid deposition, fibrosis, and nonalcoholic fatty liver disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ). Another tumor suppressor, regulator of G protein signaling 6 ( RGS6 ), is upregulated in the liver of NAFLD patients, forms a complex with ATM in the liver, promotes ATM phosphorylation, and drives hepatic steatosis ( 44 , 45 ). A study confirmed that hepatic RGS6 increases oxidative stress and inflammation, which drive lipid deposition, fibrosis, and nonalcoholic fatty liver disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulation by non-coding RNAs, TGF-β can exert its influence on EMT by other effectors; G-protein regulator signaling 6, a tumor suppressor protein that negatively regulates TGF-β-induced EMT in NSCLC, and its low expression was associated with poor survival, which suggests that it is a possible LC prognostic marker [ 37 ]. In addition to QKI-5, an important protein involved in the RNA signal transduction, it has been shown that this protein decreased in metastatic lung adenocarcinoma, and its overexpression inhibits TGF-β-induced EMT-mediated invasion and metastasis via TGFβRI [ 38 ].…”
Section: Tgf-β Molecular Mechanism In Lung Cancermentioning
confidence: 99%
“…The canonical function of RGS proteins is to act as GTPase-activating proteins (GAPs), accelerate GTP hydrolysis on G-protein alpha subunits, and terminate signaling pathways downstream of G protein-coupled receptors (Hunt et al, 1996). RGS proteins can have noncanonical GAP-independent functions, including the suppression of transforming growth factor beta (TGF-β)-induced EMT in non-small cell lung cancer by RGS6 (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%